Electron structure of TiO₂ composite films with noble metal nanoparticles - Busko, T.O.; Kulish, M.P.; Dmytrenko, O.P.; Vityuk, N.V.; Eremenko, A.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Thin nanocrystalline films of ТіО₂, TiO₂/ZrO₂, TiO₂/ZrO₂/SiO₂,
TiO₂/ZrO₂/SiO₂/Ag and TiO₂/ZrO₂/SiO₂/Au were prepared using the sol-gel synthesis
method. In this paper, we determined the bandgap for direct and indirect band-to-band
transitions. Optical conductivity of the films was determined using the spectral
ellipsometry method. Depending on the nanocomposite composition, optical conductivity
is of different character due to light absorption caused by the presence of the structure
intrinsic defects: oxygen vacancies (F²⁺, F, and F⁺
centers), Ti³⁺ ions and interstitial Ti
atoms. Rearrangement of the electron spectrum in these thin films due to the
aforementioned defects can improve photocatalytic activity in the UV and visible
spectral ranges.